2018
DOI: 10.1108/ijssp-03-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal differentials in street begging: the case of Ibadan municipality, Nigeria

Abstract: Purpose The purpose of this paper is to provide an insight into the relationship that exists between land use activities and street begging in Ibadan municipality, Nigeria, following the observed influence of urban land use activities on begging incidence. Design/methodology/approach Primary data were obtained through the method of direct enumeration of beggars and cursory observation of the physical and environmental compositions of the identified beggars’ locations in the study area. Findings The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…(2016), respectively, declared vagrancy as a function of socioeconomic factors, resulting from begging in the streets when individuals lose their way in unfamiliar areas. Another study reveals that individuals with mental illnesses in Nigeria beg to be self‐sustained after recovery, which is why people go missing (Hassan et al., 2020; Taiwo, 2018). This could necessitate support at recovery rather than leaving people in the hands of their families for empowerment in addition to further enquiry on vagrancy in the settings of this current study.…”
Section: Discussionmentioning
confidence: 99%
“…(2016), respectively, declared vagrancy as a function of socioeconomic factors, resulting from begging in the streets when individuals lose their way in unfamiliar areas. Another study reveals that individuals with mental illnesses in Nigeria beg to be self‐sustained after recovery, which is why people go missing (Hassan et al., 2020; Taiwo, 2018). This could necessitate support at recovery rather than leaving people in the hands of their families for empowerment in addition to further enquiry on vagrancy in the settings of this current study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of children on Nigerian streets has continued to increase exponentially (Fakoya, 2009; Obioha, 2009; Omorogiuwa, 2020; Taiwo, 2019). According to Population Reference Bureau (PRB) 2007 annual report, nearly 45% of the population of Nigeria are children under the age of 15 years, and 15 million children under the age of 14 are working and/or living on the street.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taiwo (2018) employed the theories of urban structure while examining land use and street begging. The researcher observed that certain land use types attracted or generated more street beggars than others.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative impacts of child labour on physical and social environments are noticeable in the predisposition of the children to interrupt and obstruct free flow of human and vehicular traffic and their high proclivity to generate waste (Taiwo, 2018a). Chigbu and Souzey (2002) in their study observe that child labour has implications for the survival of children, as working on and around busy roads exposes them to accidents, which can be fatal or lead to disability for the rest of their lives.…”
Section: Introductionmentioning
confidence: 99%